ANALYSIS OF MARKETING STRATEGIES TO ENHANCE SERVICE QUALITY IN ELECTRONIC REPAIR WORKSHOPS: A CASE STUDY AT NATEMU, SOUTHEAST ACEH - Ayu Julsari; Ratih Amelia; Deva Djohan; Albert; Emma Novirsari (Yayasan Bina Bisnis Nusantara Medan, 2025)
In today's competitive business environment, companies must continuously adapt to evolving consumer needs to sustain their market presence. The NATEMU Electronic Service Workshop in Southeast Aceh, operating for over 24 years, exemplifies these challenges. Despite a substantial customer base, NATEMU has recently experienced a decline in clientele due to the intensification of market competition and the emergence of new service providers. This study aims to analyze marketing strategies that can enhance service quality and restore customer loyalty. The research utilizes SWOT analysis to identify the workshop's internal strengths and weaknesses, as well as external opportunities and threats. Furthermore, the study applies the marketing mix framework (4Ps)—product, price, place, and promotion—to develop strategic initiatives. The findings reveal that while NATEMU's service quality is generally rated as good, certain aspects, particularly service assurance, require significant improvement. Enhancing promotional activities through social media platforms and optimizing the strategic location of the workshop are identified as key factors in attracting a broader customer base. The study concludes that the integration of SWOT analysis and an effective marketing mix strategy is essential for improving service quality and increasing customer satisfaction. These strategic approaches are critical for NATEMU Workshop to maintain competitiveness and achieve sustainable growth in an increasingly dynamic service industry.